Boosting Alkaline Hydrogen Evolution Electrocatalysis over Metallic Nickel Sites through Synergistic Coupling with Vanadium Sesquioxide. Issue 23 (13th November 2019) - Zhang, Xin Yu; Yuan, Haiyang; Mao, Fangxin; Wen, Chun Fang; Zheng, Li Rong; Liu, Peng Fei; Yang, Hua Gui
Abstract: For renewable and sustainable energy, developing cut‐price and high‐efficiency electrocatalysts for the hydrogen evolution reaction (HER) by alkaline water electrolysis is of paramount importance. In this study, a compound electrocatalyst composed of nickel–vanadium sesquioxide nanoparticles supported on porous nickel foam (Ni‐V2 O3 /NF) is found to exhibit electrocatalytic performance towards HER that is superior to that of the commercial Pt/C catalyst, with nearly zero onset overpotential, an extremely low overpotential of 25 mV to obtain a current density of −10 mA cm −2, a Tafel slope of 58 mV dec −1, and a good durability for 24 h in 1.0 m KOH. Theoretical calculations reveal that the presence of V2 O3 optimizes the electronic structure of active Ni components and continuously accelerates the dissociation of water molecules, which in turn improves the HER kinetics. The present work will advance the development of highly efficient nanocomposite electrocatalysts for alkaline water electrocatalysis. Abstract : Basic excellence : A compound electrocatalyst composed of nickel–vanadium sesquioxide nanoparticles supported on nickel foam is found to exhibit excellent electrocatalytic performance towards the hydrogen evolution reaction, with nearly zero onset overpotential, an extremely low overpotential of 25 mV to obtain a current density of −10 mA cm −2, a Tafel slope of 58 mV dec −1, and good durability for 24 h in 1.0 m KOH.